Intelligence Components, Learning Agility Quotient, and Work Readiness of Indonesian Islamic Education Graduates in Industry 4.0 - Mardiana, Dina (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
Integrating Islamic education with Industry 4.0 (IR4.0) presents significant challenges for graduates preparing to enter the workforce. This study aims to analyze the relationships between intelligence components (technology literacy, professional knowledge, critical thinking, problem-solving skills), learning agility quotient, and work readiness of Indonesian Islamic education graduates in the IR4.0 environment and to examine the mediating role of learning agility in these relationships. Using a quantitative cross-sectional approach, data were collected from 182 final-year Islamic education program students (96.2% aged 22-25 years; 73.1% female) and analyzed using partial least squares structural equation modeling (PLS-SEM). Results indicate that technology literacy (β=0.438, p<0.001) and problem-solving skills (β=0.345, p<0.001) positively influence learning agility, while critical thinking demonstrates an unexpected negative relationship (β=-0.229, p<0.001). Learning agility positively influences work readiness (β=0.258, p<0.001) and significantly mediates the relationships between technology literacy, problem-solving skills, critical thinking, and work readiness. These findings highlight the importance of developing learning agility as a linking mechanism between cognitive capabilities and work readiness and imply that Islamic education institutions should strengthen technology literacy and problem-solving skills while developing approaches that balance traditional values with adaptive learning capabilities to prepare graduates for the complex demands of the IR4.0 era.